Analysis of surrounding rock stability and seismic response in an extra-large surge chamber crossing a fault zone - Zhou, Wei; Chen, Wu; Lv, Yanan; Qu, Yongxiao; Li, Bo; Xiong, Qingrong; Wang, LiGe (Frontiers in Earth Science, 2025)
This study presents a comprehensive investigation of the static-dynamic stability of an extra-large surge chamber intersecting an active fault zone—a critical engineering challenge in modern hydropower infrastructure. Through three-dimensional numerical modeling (FLAC3D), we systematically quantified excavation-induced instability mechanisms and evaluated a deep-surface synergistic support system. Unsupported excavation simulations revealed severe instability with radial displacements up to 0.475 m, a 20 m plastic zone, and tangential stress loss of 65%–75%. The deep-surface synergistic support system—comprising prestressed anchor cables, systematic bolts, and shotcrete—reduced displacement by 94.5%, confined the plastic zone to ≤5 m, and restored tangential stresses to 70%–85% of in-situ values. Under the design earthquake (0.175 g horizontal, 0.1167 g vertical), displacement and stress increments remained <10% and <5% of static values, respectively. Plastic zone growth was limited to 3.8%, with all support elements operating within safe limits. This research validates a methodology for designing resilient underground infrastructure in fault-affected environments, providing critical insights for underground chamber design in complex geological settings previously considered unsuitable for large-scale development, with direct applications to hydropower engineering in tectonically active regions.